Integrasi Islam dan Kebudayaan Jawa dalam Kesenian Wayang - Devi Liasari; Badrun Badrun (Local History & Heritage, 2022)
Puppets are culture product which contain aesthetic arts inside them and they serve as a show and life guidance. Puppets are close with Javanese culture, because by learning and understanding puppets, it is become a requirement for absorbing Javanese culture. When religion enters the cultural field, religion becomes the heart of culture. Islam tried to incorporate its moral values within Javanese culture through puppets without eliminating its essence, so it creates integration of religion and culture. The writer is interested to examine and analyze the study of integration between Islam and Javanese culture within puppet arts, through this study the writer knows many significances and life values contained within puppets.